ЎҚУВЧИЛАРНИ АХБОРОТ-ТЕХНОЛОГИЯЛАР СОҲАСИДАГИ КАСБЛАРГА МАҚСАДЛИ ЙЎНАЛТИРИШ - Эшдавлатов, Ф. (SCIENCE and SOCIETY, 2021)
The article analyzes the fact that the target orientation of students to professions in the field of information technology, employment of school graduates, training of highly qualified specialists in the field of information technology is an important factor in the development of our economy.
Keywords: career guidance; IT parks; information technology; digital economy; international experience; educational practice; international labor market